Fitness and wellness - Hoeger, Werner W. K. (Morton, 1999)
The importance of physical fitness & wellness. Assessment of physical fitness. Exercise prescription. Evaluating fitness activities. Nutrition for wellness. Weight management. Stress management and assessment. A healthy lifestyle approach. Relevant questions and answers about fitness and wellness.